EPT graphs on bounded degree trees - Alcón, Liliana Graciela (2014)
An undirected graph Gis called an EPT graphif it is the edge intersection graph of a family of paths in a tree. In this paper, we answer negatively the question posed by Golumbic et al. [4]: Canany EPT graph without induced cycles of size greater than h be represented in a host tree with maximum degree h?